Pengembangan Bahan Ajar Digital Book Pada Materi Statistika Untuk Mahasiswa Pendidikan Islam Anak Usia Dini : Indonesia - Zulfikar, Dede; Hilliyani (Ar-Riyadhiyyat: Journal of Mathematics Education, 2025)
Learning that facilitates non-mathematics students in creating a new learning atmosphere has not yet aligned with the characteristics and availability of digital-based learning tools. This study aims to develop digital book-based teaching materials designed to support and enhance the learning experience of students in the Early Childhood Islamic Education (PIAUD) Study Program. These materials are tailored to meet the needs of PIAUD students and can be easily accessed online through laptops and smartphones. This development research employs the ADDIE method, which consists of five stages: Analyze, Design, Develop, Implement, and Evaluate. The developed teaching materials were validated by experts, including media and material experts. Data were collected using validation sheets consisting of expert validations and response questionnaires. The validation results from media experts yielded an average score of 88.37%, categorized as very valid, while the validation results from material experts yielded an average score of 88.05%, also categorized as very valid. After the materials were deemed valid, they were tested on students. The responses from the distributed questionnaires indicated that the developed materials were feasible for use. Moreover, the digital book-based teaching tools were practical and effective in providing a learning experience where students could easily comprehend each topic presented, supported by embedded instructional videos.